PENGARUH TOTAL ASSET TURNOVER (TATO), DEBT TO EQUITY RATIO (DER) DAN RETURN ON INVESTMENT (ROI) TERHADAP HARGA SAHAM PADA PT. HM. SAMPOERNA. Tbk DI BURSA EFEK INDONESIA PERIODE 2006 – 2014 - Atikah Atikah; Yunan Surono (Universitas Batanghari Jambi, 2015)
The purpose of the Company is Prosperity Maximizing Shareholder Or Maximize the Value of the Company. If the Company is Providing Value Investing Now Bigger From Investing, So Will Increase Corporate Value. Total Asset Turnover